DIGITAL LITERACIES AS SOCIAL PRACTICES IN COLLABORATIVE LEARNING: TELETANDEM AND MEANING-MAKING - Souza, Fábio Marques; Ferreira da Silva, Rivaldo; Lins, Élida Ferreira; Macedo Junior, Helenildo Arruda de Macedo Junior (Saberes: Revista interdisciplinar de Filosofia e Educação, 2024)
Digital literacies (DLs) encompass sets of literacy practices that are continuously supported, interwoven and adapted through the use of digital devices for specific purposes. It occurs in sociocultural contexts with geographical and temporal limitations, as well as in those shaped by electronically mediated interactions. In view of this, this article aims, from a critical perspective, to discuss the influences of Digital Literacy and the use of Audiovisual Resources on the mediation and practice of Teletandem. Therefore, this study is a qualitative research with bibliographic procedures. To support our arguments, we base ourselves on: Almeida Filho (1993), Benedetti (2010), Souza (2015), Rammé (2014), Rojo (2010), Cope, Kalantzis e Pinheiro (2020), Silva (2022), Arroio and Giordan (2006), Lemke (2010), Buzato (2006, 2009), Kenski (2007), among others. As a result, it was found that audiovisual resources enable the full development of the interactants' LDs and the construction of meanings.